Penerapan Pendekatan Supervisi Kolaboratif Untuk Meningkatkan Kompetensi Profesional Guru SDN Brudu Jombang - Maisaroh, Siti (Universitas Nusantara PGRI Kediri, 2020)
This study aims to describe the development of the collaborative supervision process to improve the professional competence of teachers at SDN Brudu Jombang and increase the professional competence of teachers at SDN Brudu Jombang after the collaborative supervision approach was applied. This type of research is School Action Research. The subjects of the study were SDN Brudu teachers totaling 9 people, the object of this research was the professional competence of teachers. This research was conducted in two cycles (cycle 1 and cycle 2), the results showed that with a collaborative supervision approach the average professional competence of teachers increased in the pre-cycle of 74.88 with sufficient criteria, in the first cycle of 79.77 with sufficient criteria and in cycle 2 of 87.55 with good criteria. So, it can be concluded that the professional competence of teachers at SDN Brudu Jombang can be improved through the application of a collaborative supervision approach.